Plans and specifications for a veterinary science building at the Kansas State Agricultural College - Porter, Harry E. (My University, 1907)
Introduction: This contract covers the erection and completion of a Veterinary Science building for the Kansas State Agricultural College, at Manhattan, Kans. It includes the furnishing of all materials and labor necessary for the erection and completion of the building, though every item involved may not be specially mentioned in the specifications. The heating, plumbing and electrical work will be done by the College. The contractor must in no way hinder this work and is expected to take reasonable care of it. The specifications and drawings are part and parcel of the contract and are to be construed according to their full intent, meaning and spirit, whether taken separately or together. The drawings and specifications taken conjointly shall be considered as explaining each other, and descriptive of the necessary work to be performed under the contract.
Specifications of material and labor required for the erection and completion of a veterinary science building to be located at the Agricultural College, Manhattan, Kansas
Citation: Porter, Harry E. Plans and specifications for a veterinary science building at the Kansas State Agricultural College. Senior thesis, Kansas State Agricultural College, 1907.
Morse Department of Special Collections
Keywords: Veterinary Science Building; On-Campus Construction; Kansas State University; Architectural Design; Interior Floor Plans; Exterior Design; Theses